Manajemen Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di Mts Ibnu Sina Karawang - Ditya Nur Azzahra; Sya’roni Ma’shum; Muhamad Taufik Bintang Kejora (Peneliti.net, 2022)
This study aims to determine the implementation of principal management in improving the quality of education at Mts Ibnu Sina. The method in this study uses a qualitative method. Research location at Mts Ibn Sina. The research participant is the principal of the school. The object of research is management aspects including planning, organizing, implementing and evaluating. The results of this study indicate that the principal as a manager plays a role: the principal of Mts Ibnu Sina makes plans to improve quality, namely holding a meeting at the beginning of the year or what is often referred to as the School Annual Work Meeting (RAKER) Together with teachers, employees, and stakeholders at Mts Ibnu Sina. The organization carried out by the principal of Mts Ibnu Sina by dividing the duties of employees (Tupoksi) according to their responsibilities. In practice, the principal provides direction and motivation for teachers to teach using various methods and provides fair treatment to teachers if the teacher gets an achievement. The principal of Mts Ibnu Sina did a gradual evaluation. The evaluation is carried out once every 1-2 months by holding meetings with fellow teachers and school principals, and the foundation's overall evaluation of education management is of course.